KEPUASAN KONSUMEN TERHADAP ATRIBUT SAYURAN HIDROPONIK CASA FARM BANDUNG - Irfan Nasrulloh; Trisna Insan Noor (Universitas Galuh Ciamis, 2021)
Vegetables is one of the leading commodities because it has high economic value. Vegetable consumption is needed by the body as one of the sources of vitamins, minerals and fiber in achieving a healthy diet in accordance with the recommendations of balanced nutrition guidelines to obtain optimal health. Casa Farm Hydroponics is one of the producers of hydroponic vegetables from Bandung that has been established since 2014. In the face of competition for services becomes a very important things, because the service that is not maximal can reduce the number of consumers. Therefore, improved service quality is needed in an effort to attract consumers to buy vegetables at Casa Farm Hydroponics. This research was conducted by distributing 35 questionnaires and carried out calculations by Importance Performance Analysis (IPA) method and Customer Satisfaction Index (CSI) method. IPA method aims to determine the value of interest level and performance level of Casa Farm hydroponic vegetable attributes. CSI method that aims to know the overall level of customer satisfaction. From the calculation of IPA method in Cartesian Diagram of 13 attributes there are 5 attributes that require improvement and improvement, namely attributes number 7, 9, 10, 11, and 13. The calculation result of CSI method in Casa Farm hydroponic vegetable attribute scored by 89%, the score is in a scale range of 81% < CSI ≤ 100% which means that the respondent's consumer satisfaction level belongs to the category of very satisfied.